Rapid Molecular Diagnostics to Inform Empiric Use of Ceftazidime/Avibactam and Ceftolozane/Tazobactam Against Pseudomonas aeruginosa: PRIMERS IV. (20th September 2018) - Evans, Scott R; Tran, Thuy Tien T; Hujer, Andrea M; Hill, Carol B; Hujer, Kristine M; Mediavilla, Jose R; Manca, Claudia; Domitrovic, T Nicholas; Perez, Federico; Farmer, Michael; Pitzer, Kelsey M; Wilson, Brigid M; et al.
Abstract: Background: Overcoming β-lactam resistance in pathogens such as Pseudomonas aeruginosa is a major clinical challenge. Rapid molecular diagnostics (RMDs) have the potential to inform selection of empiric therapy in patients infected by P. aeruginosa . Methods: In this study, we used a heterogeneous collection of 197 P. aeruginosa that included multidrug-resistant isolates to determine whether 2 representative RMDs (Acuitas Resistome test and VERIGENE gram-negative blood culture test) could identify susceptibility to 2 newer β-lactam/β-lactamase inhibitor (BL-BLI) combinations, ceftazidime/avibactam (CZA) and ceftolozane/tazobactam (TOL/TAZO). Results: We found that the studied RMD platforms were able to correctly identify BL-BLI susceptibility (susceptibility sensitivity, 100%; 95% confidence interval [CI], 97%, 100%) for both BLs-BLIs. However, their ability to detect resistance to these BLs-BLIs was lower (resistance sensitivity, 66%; 95% CI, 52%, 78% for TOL/TAZO and 33%; 95% CI, 20%, 49% for CZA). Conclusions: The diagnostic platforms studied showed the most potential in scenarios where a resistance gene was detected or in scenarios where a resistance gene was not detected and the prevalence of resistance to TOL/TAZO or CZA is known to be low. Clinicians need to be mindful of the benefits and risks that result from empiric treatment decisions that are based on resistance gene detection in P. aeruginosa, acknowledging that such decisions are impacted by the prevalence of resistance, which varies temporally and geographically. Abstract : A collection of 197 Pseudomonas aeruginosa was used to determine whether 2 rapid molecular diagnostics could predict resistance to ceftazidime/avibactam and ceftolozane/tazobactam. The greatest potential was observed when a defined resistance gene was detected or when not detected and resistance prevalence was low.